Enhancing Early Reading Skills in Slow Learner Students Through an Integrated Global-Direct Instruction Method - Rahmawati, Rahmawati; Pujaningsih, Pujaningsih (Papanda Publisher, 2025)
Slow learner students face significant challenges in early reading acquisition due to cognitive processing limitations and reduced statistical learning efficiency. This study investigated the effectiveness of an integrated Global-Direct Instruction (GLODIN) method for improving CVCV pattern word reading among fourth-grade slow learner students. A classroom action research design following the Kemmis and McTaggart model was implemented over six weeks with three slow learner participants (IQ 70-89) at SDN 009 Sangatta Utara. The intervention consisted of two cycles: Cycle I (four sessions) and Cycle II (three sessions) incorporating systematic modifications based on reflective analysis. The GLODIN method integrated global reading approaches with direct instruction principles through structured 12-step procedures using picture-word cards and letter manipulation activities. Data collection utilized observation protocols for instructional fidelity and student participation, plus 15-item oral reading assessments measuring CVCV word accuracy. All participants demonstrated substantial improvement from baseline to final assessment (mean improvement: 51.11%). Individual gains ranged from 50% to 53.33%, with all students achieving the 85% mastery criterion. Student participation increased by 18.11% across cycles, while instructional quality improved by 12.67%. Cycle I yielded 76.66% mean performance, progressing to 92.22% in Cycle II. The GLODIN method successfully addressed dual-route reading acquisition by strengthening both lexical recognition and phonological decoding pathways. Results challenge deficit-based perspectives regarding slow learner capabilities, demonstrating that systematic multisensory instruction with increased repetition can overcome cognitive processing limitations. The integration of global and direct instruction methodologies represents a novel contribution advancing beyond previous isolated approaches, providing educators with a validated framework for inclusive reading instruction.